A Double-Blind randomized placebo controlled clinical trial on the supplementation of Probiotics in the First six months of Life in Asian Infants at risk of allergic diseases - Effects on Development of Allergic Disease and Safety aspects with two year follow-up - SOH SHU E (2010)
Ph.D